Creating business plans : gather your resources, describe the opportunity, get buy-in, - Harvard Business School (20-minute manager series, 2014)
A well-crafted business plan generates enthusiasm for your idea and boosts your odds of success--whether you're proposing a new initiative within your organization or starting an entirely new company. Creating Business Plans quickly walks you through the basics. You'll learn to :Present your idea clearly. Develop sound financial plans. Project risks--and rewards. Anticipate and address your audience's concerns. Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly read and apply, for ambitious professionals and aspiring executives--from the most trusted source in business.